Implementation of Prevention and Control of Anemia in Central Sulawesi - Taqwin Taqwin; Putri Mulia Sakti; Linda Linda; Fahmi Hafid; Nasrul Nasrul; Anna Veronica Pont; Widya Pani; Kadar Ramadhan (Poltekita: Jurnal Ilmu Kesehatan, 2025)
This study evaluates anemia prevention and control measures among adolescent girls in Central Sulawesi, Indonesia, where anemia remains a pressing public health issue. Conducted from March to June 2024 in junior and senior high schools in Donggala and Poso, the cross-sectional study surveyed 384 girls using a structured questionnaire. Ethical approval was granted, and informed consent was obtained from participants. The study revealed a prevalence of anemia at 54.71%, with 79.43% of affected girls reporting iron supplement intake. Significant factors associated with anemia included daily consumption of fortified wheat flour (p = 0.010, PR 1.75), mid-upper arm circumference (MUAC) (p = 0.011, PR 1.74), and negative attitudes toward anemia prevention (p = 0.043, PR 1.54). Despite the high percentage of girls taking iron supplements, anemia remains prevalent, indicating gaps in current prevention efforts. The findings highlight the need for enhanced food fortification, better nutritional monitoring, and educational initiatives to shift attitudes and behaviors. Future research should investigate the long-term effectiveness of these interventions to improve public health outcomes.